Distribution pattern and its correlation for oral cancer rate and human development rank for countries: An ecological approach - Jacob Kuruvilla; Kesavan Rajasekharan Nayar (Wolters Kluwer Medknow Publications, 2021)
Introduction: There is a general interpretation that the distribution and pattern of various cancers exhibit geographical variations between developed and developing countries. However, as far as oral cancer is concerned, these differential patterns of distribution are not much documented. Aim and Objective: This review is aimed to bring in the existence of geographical disparities and its pattern for oral cancer incidence and mortality. The objectives of this review are: (1) To compare and comment on the trends in estimates for oral cancer incidence and mortality for the years 2002, 2008, and 2012. (2) To correlate oral cancer incidence and mortality values for 2012 with the human development index (HDI) scores for 2012 for each country. Design: Ecological approach and entire review was carried out using two secondary data sets, and they were (i) Age-standardized oral cancer incidence and mortality value for all countries published by the International Agency on Cancer Research for the years 2002, 2008, and 2012. (ii) HDI score for all countries for the year 2012 released by the United Nations Development Program. Results: A diametric pattern of distribution was observed across the two strata of countries. When developed countries have higher rates for incidence, low developed countries have higher rates for mortality.